2017
DOI: 10.1017/jmech.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

Motion Model and Speed Control of the Cross-Stream Active Mooring System for Tracking Short-Term Meandering to Maximize Ocean Current Power Generation

Abstract: This paper analyzes the speed of lateral movement of the Cross-stream Active Mooring (CSAM) system in an ocean current and its control methods in order to study the system's capability of tracking short term meandering of ocean currents for maximizing power generation capacity. The CSAM concept for marine current power features a hydro sail system that can deploy generator turbines transversely across streams in a marine current. The hydro sail system can further adjust the horizontal position of the turbines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The technology of deep-water generator lies in the high-efficiency conversion technology of generator. With the breakthrough of underwater low-speed generator, marine energy development will also produce a corresponding leap [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The technology of deep-water generator lies in the high-efficiency conversion technology of generator. With the breakthrough of underwater low-speed generator, marine energy development will also produce a corresponding leap [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the SPAR type has better performance for a multi-arrayed system. More recently, Tsao and Feng [14] have developed the cross-stream active mooring system to adjust the horizontal position of a current turbine in order to track fast streams and thus increase the power generation capacity.…”
Section: Introductionmentioning
confidence: 99%